Can smart homes extend people with Alzheimer's disease stay at home?. Issue 1 (20th March 2017) - Brunete González, Alberto; Selmes, Micheline; Selmes, Jacques
Abstract : Purpose: The purpose of this paper is to analyse the needs of people with Alzheimer's disease and their caregivers in terms of information and communications technology (ICT) and home automation, and how to foster the use of smart devices in their homes and also, to determine whether the use of ICT can extend people with Alzheimer's disease stay at home in the first stages of the illness, while facilitating their caregivers' tasks. Design/methodology/approach: Groups of caregivers, ICT researchers and Alzheimer's disease experts were gathered to discuss the utility of several solutions. Sessions were grouped into four topics: safety, leisure, activities of daily living and friendly atmosphere. In total, 23 ICT-based solutions to improve life at home of people with Alzheimer's disease were analysed and grouped under "no interest", "some interest" and "very interesting". Caregivers rated these solutions and suggested improvements to them. Findings: In total, 18 out of 23 proposals were considered "very interesting", meaning that caregivers considered that they could truly improve the lives of people with Alzheimer's disease. Caregivers also suggested how to progressively introduce these technical solutions into their homes. Originality/value: ICT and home automation advances could be very useful if used conveniently. Caregivers consider that smart homes can help people with Alzheimer's disease in the security, leisure and daily tasks fields, increasing the time they can live alone in their own homes.